2021
DOI: 10.26417/501ibq23c
|View full text |Cite
|
Sign up to set email alerts
|

Augmented and Mixed Reality in Language Learning

Abstract: The use of Extended Reality technologies in education, and especially in language learning, has attracted the interest of language experts for the last 15 years. However, the recent technological progress as well as the simultaneous dramatic reduction of the cost of the necessary hardware has led to an impressive growth of the XR market, creating, thus, new perspectives concerning the adoption of XR technologies in education. The educational XR market is also growing very fast, not only thanks to the offer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Tämän ansiosta käyttäjä pystyy hyödyntämään AR-teknologiaa sellaisten taitojen tai sisältöjen opiskeluun, jossa on tarpeen säilyttää näköyhteys omaan kehoon, kuten esimerkiksi kirjoitustaidon tai viittomakielen opiskelussa (Parmaxi & Demetriou 2020). Kuten virtuaalitodellisuus, myös AR-teknologia ja sisältöjen uudenlainen esitystapa on nähty oppijan motivaatiota ja opetukseen sitoutumista lisäävänä vaihtoehtona (Panagiotidis 2021;Thorne ym. 2015).…”
Section: Virtuaaliteknologia Uudenlaisten Oppimisympäristöjen Mahdoll...unclassified
“…Tämän ansiosta käyttäjä pystyy hyödyntämään AR-teknologiaa sellaisten taitojen tai sisältöjen opiskeluun, jossa on tarpeen säilyttää näköyhteys omaan kehoon, kuten esimerkiksi kirjoitustaidon tai viittomakielen opiskelussa (Parmaxi & Demetriou 2020). Kuten virtuaalitodellisuus, myös AR-teknologia ja sisältöjen uudenlainen esitystapa on nähty oppijan motivaatiota ja opetukseen sitoutumista lisäävänä vaihtoehtona (Panagiotidis 2021;Thorne ym. 2015).…”
Section: Virtuaaliteknologia Uudenlaisten Oppimisympäristöjen Mahdoll...unclassified
“…(5) special education [40]. Some studies have explored the effectiveness of technology application in education, such as biological experiments [41], and education related to art [42], language [43], music [44], healthcare [45], physical [46,47], and blended education [48].…”
Section: Application Of Extended Reality In Educationmentioning
confidence: 99%
“…Some hold that XR educa tional application scenarios relate to: (1) smart education product design; (2) implementa tion of game-based learning; (3) construction of smart learning environment; (4) design education; (5) special education [40]. Some studies have explored the effectiveness of tech nology application in education, such as biological experiments [41], and education re lated to art [42], language [43], music [44], healthcare [45], physical [46,47], and blended education [48].…”
Section: Application Of Extended Reality In Educationmentioning
confidence: 99%
“…Frost, J et al applied Mixed Reality (MR) technology to nursing education and found that the approach promoted nursing students' clinical judgment and skills in noticing patients' physical cues [20]. Panagiotidis, P argued that technological advances in wireless and cellular networks have facilitated XR experiences to be more immersive and accessible to both local and distance education, and he proposed that the use of Augmented Reality (AR) and Mixed Reality (MR) technologies in language education and explores their future prospects [21]. Ivkovic, I and Franch, S incorporate MR technologies into engineering education, which contribute to the enhancement of information about digital artifacts, three-dimensional objects, and views of audio and video, create enhanced blended learning environments, and significantly improve engineering students' engagement and learning outcomes [22].…”
Section: Introductionmentioning
confidence: 99%